Examining the Effect of Work and Non-Work Domain on School Counselor Career Self-Regulation Moderated Career Self-Management - Abdullah Sinring; Nur Fadhilah Umar (JURKAM: Jurnal Konseling Andi Matappa, 2023)
This study aims to investigate the effect of work and non-work aspects on career self-regulation of school counselors, by considering the moderating role of career self-management. The data was obtained through a questionnaire filled out by 112 counseling teachers spread across several districts in South Sulawesi. The research questionnaire developed from Toeri Hirchi with contextual role, resources, and barries aspects has been tested by exploratory factor analysis and CFA, other research questionnaires are self-regulation scale and career self-management scale. The data analysis technique used is path analysis to examine the relationship between research variables. The results of the study show that work and non-work aspects directly influence the self-regulation of school counselor careers. In addition, it was found that work and non-work aspects also have an indirect influence on career self-regulation through career self-management. This finding shows that these factors are interrelated and have an important role in the regulation and management of school counselor careers. The implication of this research is the importance of paying attention to aspects of work, non-work, and career self-management in an effort to increase school counselor career self-regulation. With a better understanding of these factors, steps can be taken to improve the quality of services in school counseling and support successful careers for counselors.